Evaluation of a Web-Based Professional Development Program (Project ACE) for Teachers of Children With Autism Spectrum Disorders. (August 2015) - Rakap, Salih; Jones, Hazel A.; Emery, Alice Kaye
This article describes the development, implementation, and second-year evaluation of Project Autism Competencies for Endorsement (ACE), a web-based professional development (PD) program that is designed to train teachers currently working in the field to meet the unique and diverse needs of children with autism spectrum disorders (ASDs). A description of the rationale for the project and an overview of the program of study are followed by the presentation of the second-year evaluation activities and their results. Preliminary findings of this study suggested that the web-based PD program was effective in helping teachers develop and improve their competencies, knowledge, and skills. Moreover, teachers felt comfortable using the teaching strategies they learned in the program and reported some application of these strategies in their practices. Also, most teachers reported their satisfaction with the web-based courses offered in the program. Implications for the future research and practice are presented.